2012
DOI: 10.1103/physreva.86.032117
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal multipartite correlations from local marginal probabilities

Abstract: Understanding what can be inferred about a multiparticle quantum system given only the knowledge of its subparts is a highly nontrivial task. Clearly, if a global system does not contain an information resource of some kind, neither do its subparts. For the case of entanglement as an information resource, it is known that the converse of this last statement is not true: Some nonentangled reduced states are only compatible with global states which are entangled. We extend this result to correlations and provide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 26 publications
4
38
0
Order By: Relevance
“…In this work we present several results that complement and generalize those of [14][15][16]. We offer a brief summary of our findings in Table I.…”
Section: Introductionsupporting
confidence: 72%
“…In this work we present several results that complement and generalize those of [14][15][16]. We offer a brief summary of our findings in Table I.…”
Section: Introductionsupporting
confidence: 72%
“…Then, it is natural to expect that Bell inequalities based on only few-body correlations are, in general, weaker in revealing nonlocality than those constructed from high-order correlations (that is, correlations among many of the observers). Whereas Bell inequalities involving correlations among all but one parties have been constructed in [49][50][51], thus proving that all-partite correlations are not necessary to reveal nonlocality, here we have to consider the more demanding question of whether nonlocality detection is possible for systems of an arbitrary number of parties from the minimal information achievable in a Bell test, i.e., two-body correlations. We answered this question positively in Ref.…”
mentioning
confidence: 99%
“…We shall use the property of monogamy of correlations [7]. Another approach has recently been put forward by Würflinger et al [8] who have shown that some non-entangled reduced density operators can be linked with global entangled states.…”
mentioning
confidence: 99%